2017
DOI: 10.1021/acschembio.7b00370
|View full text |Cite
|
Sign up to set email alerts
|

Novel Class of Potent and Cellularly Active Inhibitors Devalidates MTH1 as Broad-Spectrum Cancer Target

Abstract: MTH1 is a hydrolase responsible for sanitization of oxidized purine nucleoside triphosphates to prevent their incorporation into replicating DNA. Early tool compounds published in the literature inhibited the enzymatic activity of MTH1 and subsequently induced cancer cell death; however recent studies have questioned the reported link between these two events. Therefore, it is important to validate MTH1 as a cancer dependency with high quality chemical probes. Here, we present BAY-707, a substrate-competitive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 16 publications
2
79
1
Order By: Relevance
“…Recent reports indicated that cancer cells were also heavily dependent on functional MTH1 to maintain stemness and tumorigenesis [37,38]. Several small molecular inhibitor of MTH1 including TH588, BAY707 and S-crizotinib were developed and their anti-tumor activities looks promising [27,39,40]. For TH588, some researchers questioned its target speci city as this agent also possesses microtubule-modulating activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicated that cancer cells were also heavily dependent on functional MTH1 to maintain stemness and tumorigenesis [37,38]. Several small molecular inhibitor of MTH1 including TH588, BAY707 and S-crizotinib were developed and their anti-tumor activities looks promising [27,39,40]. For TH588, some researchers questioned its target speci city as this agent also possesses microtubule-modulating activity.…”
Section: Discussionmentioning
confidence: 99%
“…While the underlying biology behind MTH1's involvement in tolerance to oncogene-induced oxidative stress is emerging [87,[105][106][107][108][109][110][111], the biology of small molecule MTH1 inhibitors remains unresolved in the literature. Several MTH1 inhibitor series fail to kill cancer cells, despite apparent successful target engagement in cells [112][113][114][115]. A key observation is that the anti-cancer effect seems to be coupled to accumulation of oxidized bases in the genome, as the MTH1 inhibitors that fail to accumulate oxidized bases also fail to kill cancer cells [96,115].…”
Section: Sensitization To Endogenous Cancer-specific Dna Damagementioning
confidence: 99%
“…Several MTH1 inhibitor series fail to kill cancer cells, despite apparent successful target engagement in cells [112][113][114][115]. A key observation is that the anti-cancer effect seems to be coupled to accumulation of oxidized bases in the genome, as the MTH1 inhibitors that fail to accumulate oxidized bases also fail to kill cancer cells [96,115]. Since these oxidized bases are substrates for BER, it follows that inhibitors to BER could be used to either potentiate the effect of MTH1 inhibitors, or to kill subsets of cancers where the cancer cell relies more on downstream BER than MTH1 to maintain viability.…”
Section: Sensitization To Endogenous Cancer-specific Dna Damagementioning
confidence: 99%
“…Therefore, MTH1 has been explored as a potential cancer therapeutic target, and indeed inhibition of MTH1 by small molecules TH588 and TH287, the first-in-class nudix hydrolase family inhibitors, Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry causes incorporation of oxidized dNTPs in cancer cells leading to DNA damage, cytotoxicity and therapeutic responses in patient-derived mouse on xenografts [54,55]. Unfortunately, this finding has been seriously challenged by recent studies demonstrating that MTH1 is dispensable for cancer cell survival [56,57]. Thus, it remains to be established how much cancer cells really rely on MTH1 activity.…”
Section: Mth1 Mth2mentioning
confidence: 99%